Calcium and L-histidine interaction on growth improvement of three tomato cultivars under nickel stress - Mozafari, Hossein (Acta Biologica Szegediensis, 2013)
Nickel is considered to be an essential micronutrient for many plants; however, it is very toxic at excess concentration. In this investigation the interaction between L-histidine (His) and calcium on improvements of growth and K+ nutrition was studied under Ni2+ stress in hydroponic media in 3 tomato cultivars (Cal-J N3, Early Urbana Y and Petoearly CH) from Iran. The treatments contained Ca2+ (400 and 700 μM), L-histidine (0 and 300μM) and NiSO4 (0, 150 and 300 μM). The following parameters were determined: root and shoot length, fresh weight, pigment concentration, leaf area index, K+ accumulation, reducing sugars, proline, free amino acids (FAA) and leaf relative water content (RWC). The results showed that Ni2+ treatments significantly decreased the shoot and root length, the pigment content of leafs and the K+ content of root and shoot in all cultivars, whilst application of Ca2+ and His elevated these growth and nutritional parameters irrespectively of the presence of Ni. The effect of Ca2+ on increasing of leaf area and other parameters in Early Urbana Y and Cal-J N3 cultivars was more pronounced than in Petoearly CH cultivar. Therefore, application both Ca2+ and His can affect on nutrition improvement and increasing of the tolerance and growth of agronomic plants under Ni2+ stress.